A new species of Protonemura (Plecoptera: Nemouridae) from China and new images of three other species of the genus - Zhao, Meng-Yuan; Du, Yu-Zhou (Zootaxa, 2020)
A new nemourid species, Protonemura longispina sp. nov. from Sichuan Province of southwestern China is described. The outer lobe of the paraprocts with numerous long spines and the basal portion divided into two lobes, distinguishes the new species from all congeners. New images of three other species, P. bidigitata Du & Wang, P. biintrans Li & Yang, and P. macrodactyla Du & Zhou are given. Additionally, a key to the adult males of Protonemura known from China is provided.